Proposal of an integrated platoon‐based Round‐Robin algorithm with priorities for intersections with mixed traffic flows. Issue 9 (17th June 2021) - Moradi, Hossein; Sasaninejad, Sara; Wittevrongel, Sabine; Walraevens, Joris
Abstract: The growth of vehicle ownership has necessitated the adoption of new approaches to cope with the arising problems. In this regard, while technological advancement in connected and automated vehicles (CAVs) leads to a new source of information upon which effective intersection control mechanisms can be built, it also necessitates considering the issue of mixed traffic, on the one hand, and enhancing current infrastructures, on the other. This paper first proposes a framework, which enhances pre‐timed signals to incorporate CAVs and wireless communications. In this framework, Round‐Robin has been selected as the main algorithm treating vehicles' platoons as the units. Dealing with mixed traffic conditions and embedding an algorithm for prioritization of special vehicles are also discussed in the context of this framework. The result is a proposal of the Platoon‐based Round‐Robin algorithm with Priorities (the PRRP‐framework ). This framework is further integrated into a speed advisory system to mutually augment each other's functions to provide for as much continuous movement of mixed traffic as possible. Performance indices obtained from the corresponding simulations show that while the PRRP‐framework is promising even with a low proportion of the CAVs, it is possible to get out considerably more benefits in the case of the proposed integration.